Study of Sulfate Concentration of Mula-Mutha Rivers in Pune (Maharashtra) - Kanase, D.G.; Jadhav, S.D.; Jawale, R.W.; Kadam, M.S. (Asian Journal of Chemistry, 2010)
The sulfate concentration of Mula-Mutha rivers was assessed from Garware Causeway to Koregaon Park. The samples were collected along the course of rivers and it was observed that the rivers receive industrial effluents and domestic waste along with the heavy loads of agricultural run-off. As a whole the River Mutha is a more polluted river than Mula.